The prediction of colorectal cancer using anthropometric measures: A Swedish population-based cohort study with 22 years of follow-up. Issue 9 (November 2019) - Andreasson, Anna; Hagström, Hannes; Sköldberg, Filip; Önnerhag, Kristina; Carlsson, Axel C; Schmidt, Peter T; Forsberg, Anna M
Background: Obesity is a risk factor for colorectal cancer (CRC). Objective: The objective of this article is to investigate whether anthropometric measures reflecting visceral obesity are better predictors of CRC than body mass index (BMI). Methods: Data were analysed from the Malmö Diet and Cancer study in Sweden, comprising 16, 669 women and 10, 805 men (median age 56.6 and 59.1 years) followed for a median 21.5 years. Diagnoses of CRC were identified using Swedish national registers. Cox regression was used to test the associations of BMI, waist circumference (WC), waist-hip ratio, waist-to-height ratio, waist-to-hip-to-height ratio, A Body Shape Index (ABSI) and percentage body fat with the development of CRC adjusted for age, alcohol consumption, smoking, education and physical activity in men and women. Results: None of the measures were significantly associated with an increased risk for CRC in women. WC was the strongest predictor of colon cancer (CC) in men and the only measure that was independent of BMI. ABSI was the only measure significantly associated with the risk of rectal cancer in men. Conclusions: Visceral obesity, best expressed as WC, is a risk factor for CC in men but a poor predictive marker for CRC in women.